Variation Product, Green Marketing, And Discount On Consumer Satisfaction - Niwayansari, Fira; Santoso, Adi; Wijianto, Wijianto (LPPM ISNJ Bengkalis, 2024)
This research analyses whether product variations, green marketing and discounts influence KFC consumer satisfaction at Lawu Plaza Madiun. This type of research is quantitative and uses primary data sources. The research population is all KFC consumers from active students at the Muhammadiyah University of Ponorogo, where the number cannot be known with certainty. Sampling used a non-probability sampling technique with the accidental sampling method, and sample measurement used the Hair approach, so 140 respondents were obtained. The sample measurement technique uses a Likert scale interval of 1-10. The data analysis technique uses multiple linear regression. The results of this research show that variety and green marketing have a significant positive effect on consumer satisfaction, while discounts do not have a positive effect on consumer satisfaction. Simultaneously, the variables of product variation, green marketing, and discounts influence consumer satisfaction. The results of this research can complement existing theories and be used as a reference for KFC management in increasing consumer satisfaction in terms of product variety and green marketing.